PHYSIOLOGICAL AND SOCIO-PSYCHOLOGICAL BASES OF STRESS - Gulomjonova Azizakhon Toshpolat qizi (Web of Journals Publishing, 2025)
This article examines stress and its effects on human physiology. It also provides information about the diseases that occur as a result of stress and the changes in human physiology as a result of stress. It also provides information about the social foundations of stress and the psychological foundations of stress. It explains how stress affects a person and the changes that result from stress.
Keywords: Stress, physiology, physiological effects of stress, social foundations, psychological foundations, diseases, psyche, reaction, hormones, organism, nervous system, theory.